GeMMA Activity Report 2016–2022 - Golob, Tamara (University of Maribor Press, 2023)
The primary aim of this publication is to support the dissemination of the research achievements of GeMMA Laboratory at the Faculty of Electrical Engineering and Computer Science of the University of Maribor. It follows the first survey published in 2016, and therefore, the actual book concentrates on the research results since then. The previous book, covering a period of 17 years, presented 35 R&D projects, while the new review of activities over the last 7 years covers as many as 58 projects. This growth is a good cue to introduce the secondary, equally important aim of the book. Namely, we would like to leave the track to our successors to stimulate them for even better research results, to show them, what is possible to achieve in 22 years starting from scratch with the will, hard work, orientation towards the applications, devotion to the research work, and the strong team spirit.